Genomics for transforming yam breeding - Gedil, Melaku A; Bhattacharjee, Ranjana; López Montes, Antonio José (2012)
Yam (Dioscorea spp.), a multispecies, polyploidy, and vegetatively propagated crop, is an economically important staple food for more than 300 million people in West Africa, Asia, Oceania, and the Caribbean. The five major yam-producing countries in West Africa (Bénin, Côte d’Ivoire, Ghana, Nigeria, and Togo) account for 93% of worldwide production. Dioscorea rotundata and D. alata are the species most commonly cultivated in West Africa1. The genetic improvement of yam is faced with several constraints, including the long growth cycle (about 8 months or more), dioecy, plants that flower poorly or not at all, polyploidy, vegetative propagation, heterozygous genetic background, and poor knowledge about the genetics of the crop2.